Waste-Derived Cellulose Nanocrystal–ZnO Nanocomposites Prepared by a One-Pot Green Synthesis: Structural, Optical, and Photocatalytic Properties - Prastica, Lusia; Supriyanto, Amir; Suprihatin, Suprihatin; Manurung, Posman; Suharyadi, Edy; Suciyati, Sri Wahyu (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2025)
Nanocellulose-based CNC–ZnO nanocomposites from garlic peel waste were successfully synthesized as environmentally friendly photocatalysts. This study aimed to valorize kitchen waste as a source of cellulose and combine it with ZnO through a one-pot precipitation method using CNC and Zn(NO₃)₂ as ZnO precursors. Structural, morphological, and optical properties were characterized using FTIR, XRD, SEM–EDX, XRF, and UV–Vis DRS. The XRD pattern showed a crystalline cellulose peak at 2θ ≈ 22.22° with a crystallite size of approximately 20.65 nm, while the CNC–ZnO nanocomposites showed crystallite sizes in the range of 23.93–31.12 nm. Peak shifts and broadening suggested interfacial interactions between CNC and ZnO, and the wurtzite ZnO reflections displayed a broad shoulder due to overlap with the cellulose peak and the high dispersion of ZnO within the CNC matrix. SEM–EDX analysis revealed a rod-like bundled agglomerated morphology, with the presence of Zn confirmed by EDX (39.23%) and XRF (~8.36%). The CNC–ZnO0.9 sample exhibited a band gap energy of 2.95 eV. Photocatalytic test against methyl orange (10 ppm) increased with UV irradiation time, achieving net photocatalytic efficiencies of 79.12% and 63% in the first and second cycles after 120 min, respectively. Kinetic analysis indicated that the degradation data were better described by a pseudo-second-order model with a rate constant of 0.0374 min⁻¹, indicating the role of surface interactions and the availability of active sites. These results confirmed the potential of CNC–ZnO nanocomposites derived from garlic peel waste as photocatalysts for organic dye degradation